EXAMINATION OF FERTILITY INDICATORS OF EUROPEAN BROWN HARES (Lepus europaeus) IN EASTERN HUNGARY - P. Farkas1; Sz. Kusza; P. Balogh; I. Majzinger (Journal of Animal and Plant Sciences, 2020)
A decreasing tendency in the populations of the European brown hare can be observed in the whole of Europe from the mid-1960s to the present day. Among the reasons for declining populations fertility indicators of females are also mentioned. The aim of our study was to determine the reproductive parameters of the species in eastern Hungary. During the years 2015-2016, we studied two hundred animals (121♀, 79♂). Altogether, 121 uteri (81 adult and 40 juvenile) and 79 testicles were examined. The number of placental scars showed us the number of offspring in reproductive periods. The age of hares was estimated based on the weight of dried eye lens. The number of placental scars in the general linear model was significantly affected by hunting areas, the age of animals, the interaction of the former two, and also by body weight and kidney fat indices. The age of hares, the hunting year, the effect of the interaction of the former two, and body weight seriously contributed to the weight of the testicles. Based on the number of placental scars, 70.37% of adult and 62.50% of juvenile females were proved to be capable of reproduction. One can conclude from the above that although fertility indicators may play an important role in the decreasing trend in the numbers of Hungarian brown hare populations, they are definitely not the main causes.
Keywords: Brown hare; fertility; placental scars